Exploiting Outage Performance of Wireless Powered NOMA - Dinh-Thuan Do; Chi-Bao Le (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Considering a dual-hop energy-harvesting (EH) non-orthogonal multiple access (NOMA) relaying system, this paper considers novel relaying protocol based on time power switching-based relaying (TPSR) and power switching-based relaying (PSR) schemes for two kinds of gain factors regarding amplify-and-forward mode. We introduce novel system model relaying network with impacts of energy harvesting fractions and derive analytical expressions for outage probability for the information transmission link. It confirmed that right selection of power allocation for NOMA to obtain optimal performance as compared study in two considered schemes. We also explore impacts of other key parameters of system to outage performance evaluation for different channel models. Simulation results are presented to corroborate the proposed methodology.